A ternary polymer nanocomposite film composed of green-synthesized graphene quantum dots, polyaniline, polyvinyl butyral and poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate for supercapacitor application. (March 2021) - Arthisree, D.; Madhuri, W.; Saravanan, N.; Dinesh, B.; Saikrithika, S.; Kumar, Annamalai Senthil
Highlights: A ternary polymer composite composed on PANI, PEDOT:PSS, Polypyrrole and Graphene quantum dots was prepared. A Green-synthetic approach has been adopted for the Graphene quantum dot preparation An enhanced electrical and supercapacitor (4998 Fg −1 cm −2 ) performance was noticed. Abstract: Owing to their enhanced electrical conductivity, flexibility, cost-effective and simple sampling methods, polymer-carbon nanocomposite material composed of conducting polymers have been referred as an elegant system for supercapacitor applications. Indeed, integration of engineering polymer, which has an insulating property, such as Polyvinyl butyral (PVB), into the conducting matrix is a challenging task. Herein, we introduce a ternary polymer nanocomposite composed of PVB, PANI, poly(3, 4-ethylenedioxythiophene)-poly(styrene sulfonate) (PEDOT: PSS) and green-synthesized GQD based functionally stable and optically active system for an efficient supercapacitor application. The polymer-carbon nanocomposite has been prepared as a film by the solution-casting method. The "as prepared" polymeric film was characterized using XRD, TEM, Raman, IR, UV-Vis spectroscopic, laser-optical profilometric imaging and electrochemical techniques. From the collective results, it has been revealed that there is a chemical interaction between the GQD and polymeric systems, presumably due to strong intermolecular hydrogen bonding. Supercapacitor application of the polymer nanocomposite was demonstrated by simply modifying the composite mixture on a conducting substrate-disposable screen-printed carbon electrode. Cyclic voltammetry, electrochemical impedance and galvanostatic charge/discharge experiments were performed with the modified electrode. 1 wt. % GQD loaded ternary polymer-nanocomposite is found to be an optimal system for supercapacitor application. This material showed a capacitance value of 4998 Fg −1 cm −2 Graphical abstract: Image, graphical abstract